The development of trilingual literacy in primary schools in Kenya - Mose, Peter N (Rhodes University, Faculty of Humanities, School of Languages, 2016)
The Kenyan language in education policy contemplates development of trilingual literacy skills in pupils by the end of standard three. The purpose of this study was to determine to what extent standard three pupils were literate in their mother tongue (Ekegusii), Kiswahili, and English. The study was undertaken in the context of; a language in education policy that provides for the use of mother tongues and Kiswahili (as languages of instruction) in rural and urban schools respectively up to the end of standard three, followed by a transition to an English medium from standard four; a general negative public attitude towards mother tongue instruction; and substantial empirical evidence in support of mother tongue instruction in basic education. Cummins' Linguistic Interdependence and Linguistic Threshold Hypotheses guided the study. Adopting a mixed methods approach, the study used direct classroom observations, face-to-face interviews, document analyses, and reading tests to obtain data. Thematic, content, and statistical approaches were used in data analysis. It was found that various stakeholders understand key aspects of the language in education policy differently. Secondly, efforts in mother tongue instruction in schools are not motivated by theoretical and empirical foundations; development efforts are hence ineffective and inadequate leaving majority of learners with below average literacy skills in their mother tongue by the end of standard three. Thirdly, teachers do not implement the language in education policy as spelt out in the relevant documents; the three languages have therefore been allocated various classroom functions. Fourthly, the factors that motivate the disregard of the language policy include the language of examinations and textbooks, and transition to standard four in which English is the language of instruction. Lastly, reading scores indicate that majority of pupils transiting to standard four do not possess adequate reading skills to enable them read to learn in a mother tongue, Kiswahili, and English. This is observed across rural, peri-urban, and urban schools. The study recommends that: The ministry of education conducts workshops to re-educate the relevant stakeholders on the meaning and significance of the language in education policy and the significance of mother tongue instruction in second language, literacy, and skill development. This should be followed by a re-classification of primary schools on the basis of linguistic homogeneity, or otherwise, to ensure the intention of the policy is achieved. This could include empowering individual schools to determine language of instruction in lower primary based on language predominance. Secondly, the ministry should provide relevant resources for mother tongues and Kiswahili to develop them as effective languages of instruction as recommended by various past education commission reports. Additionally, a bilingual course in teacher training colleges to equip primary school teachers for bilingualism and biliteracy development should be introduced; one implication of this is teachers giving notes and tests in the languages spelt out in the policy. Thirdly, the ministry should intensify inspection of schools to assess implementation of the policy. Fourthly, future studies should assess mother tongue literacies as well, since they determine the extent and success of second language acquisition and learning; and measures should be put to ensure English is adequately resourced and taught well. Finally, mother tongue instruction should be extended up to, at least, standard five.
Keywords: Uncatalogued